How did mental health become so biomedical? The progressive erosion of social determinants in historical psychiatric admission registers. Issue 1 (March 2021) - Handerer, Fritz; Kinderman, Peter; Timmermann, Carsten; Tai, Sara J
This paper explores the historical developments of admission registers of psychiatric asylums and hospitals in England and Wales between 1845 and 1950, with illustrative examples (principally from the archives of the Rainhill Asylum, UK). Standardized admission registers have been mandatory elements of the mental health legislative framework since 1845, and procedural changes illustrate the development from what, today, we would characterize as a predominantly psychosocial understanding of mental health problems towards primarily biomedical explanations. Over time, emphasis shifts from the social determinants of admission to an asylum to the diagnosis of an illness requiring treatment in hospital. We discuss the implications of this progressive historical diminution of the social determinants of mental health for current debates in mental health care.